Qal'at Ruwayda and the fortifications of Qatar - Petersen, Andrew; al-Naimi, Faisal (Proceedings of the Seminar for Arabian Studies, 2013)
This paper reviews the latest findings from the excavations at Ruwayda in northern Qatar. The paper will focus on results that relate to the development of the fortified enclosures, which are the principal remains visible on the site. The recent excavations have enabled us to establish a detailed relative chronology of the sequence of the fortified enclosures on the site. These results will be used as a basis for a discussion of other fortifications in Qatar. Particular attention will be paid to issues such as the size of the enclosed areas, the shape and size of the towers, the location of the gateways, and adaptation to firearms.